Prisoner radicalization and terrorism detention policy: institutionalized fear or evidence-based policy-making? - Veldhuis, Tinka (Routledge frontiers of criminal justice, 2016)
Acknowledgements -- Prisoner radicalization and terrorism detention policy -- : the making of terrorism detention policy : the terrorism wing -- Agenda setting and policy preparation -- The terrorism wing in theory -- Theoretical and empirical observations on prisoner radicalization -- A theory of prisoner radicalization -- Terrorists in the inmate hierarchy -- Terrorism detention policy in practice : implementation of the terrorism wing -- The target population -- The prison regime recapitulation -- Captivated by fear -- Fear-based terrorism detention policy -- A realist approach to rehabilitation and reintegration -- General conclusions and discussion -- Appendix A. Research methods and results (appendix to chapter 5) -- Index